High Flow Priapism in a Pediatric Patient after Circumcision with Dorsal Penile Nerve Block - Michael A. Granieri; Joseph J. Fantony; Jonathan C. Routh (Case Reports in Pediatrics)
We report the first documented case of high flow priapism after circumcision with dorsal penile nerve block. A 7-year-old male who had undergone circumcision three years before presented to our institution with a 3-year history of persistent nonpainful erections. Workup revealed a high flow priapism and, after discussion of the management options, the patient’s family elected continued observation.